Microbial biofilms for electricity generation from water evaporation and power to wearables - Liu, Xiaomeng; Ueki, Toshiyuki; Gao, Hongyan; Woodard, Trevor L.; Nevin, Kelly P.; Fu, Tianda; Fu, Shuai; Sun, Lu; Lovley, Derek R.; Yao, Jun (Nature communications, 2022)
Employing renewable materials for fabricating clean energy harvesting devices can further improve sustainability. Microorganisms can be mass produced with renewable feedstocks. Here, we demonstrate that it is possible to engineer microbial biofilms as a cohesive, flexible material for long-term continuous electricity production from evaporating water. Single biofilm sheet (~40 µm thick) serving as the functional component in an electronic device continuously produces power density (~1 μW/cm 2 ) higher than that achieved with thicker engineered materials. The energy output is comparable to that achieved with similar sized biofilms catalyzing current production in microbial fuel cells, without the need for an organic feedstock or maintaining cell viability. The biofilm can be sandwiched between a pair of mesh electrodes for scalable device integration and current production. The devices maintain the energy production in ionic solutions and can be used as skin-patch devices to harvest electricity from sweat and moisture on skin to continuously power wearable devices. Biofilms made from different microbial species show generic current production from water evaporation. These results suggest that we can harness the ubiquity of biofilms in nature as additional sources of biomaterial for evaporation-based electricity generation in diverse aqueous environments. Though water evaporation-driven electricity generation is an attractive sustainable energy production strategy, existing electronic devices suffer from poor performance or is costly. Here, the authors report sustainable biofilms for efficient, low-cost evaporation-based electricity production